Роль парентерального харчування у комплексі периоперативної інтенсивної терапії у дітей - Давидова, Анна Григорівна; Davydova, A. G. (My University, 2020)
Мета роботи: визначити терміни призначення, ефективність та безпечність парентерального харчування (ПХ) після великих хірургічних втручань у дітей. Результати. Нами була розроблена програма розрахунку ПХ у Microsoft Excel. У групі дослідження був відмічений достовірний приріст рівня білка плазми на 4-6 добу ПХ, на відміну від контрольної групи. При ПХ без інсуліну гіперглікемії не відмічалося. У групі дослідження була відмічена більш рання поява перистальтики кишечнику. Висновки. Застосування ПХ після великих хірургічних втручань є безпечним за умови дотримання коректного темпу інфузії, при правильному підборі складових ПХ. У дітей в ранньому післяопераційному періоді швидке досягнення вихідного рівня протеїнемії без використання ПХ не уявляється можливим. The difference between the child and the adult organisms is that children are more susceptible to lack of nutritional support due to the higher metabolic rate, which makes it more relevant to ensure adequate parenteral nutrition (PN) after major surgery, especially in infants. However, incorrect calculation of PN may lead to complications both in the case of its long term and in short term usage. Purpose of the work: determine the timing of appointment, effectiveness and safety of parenteral nutrition in the early postoperative period after major surgery in children. Object and methods. The study included 100 children aged 1.5 months to 17 years who had undergone major surgery on the abdominal organs. The study group consisted of patients who received parenteral nutrition in the early postoperative period (66 children), the control group – 34 children who did not receive PN. We have developed a program for calculating the PN in Microsoft Excel, which was used in drawing up an individual scheme of the PN. PN began in term from 2 to 48 hours after operative intervention, in average in 12 hours. We studied the dynamic of plasma protein and its fractures, levels of urea and creatinine, the level of glycemia and the presence of glucosuria before and during parenteral nutrition, and the terms of the persistent bowel peristalsis onset. All children underwent infusion, antibacterial therapy and adequate pain relief. Statistic methods included Mann-Whitney test using StatSoft 6.1 program. Results. In the study group, a significant (p <0.05) increase in the level of plasma protein was observed on the 4th – 6th days of PN, in contrast to the control group. A significant decrease in serum creatinine level by 26.0±7.3 μmol/l (p <0.05) from the baseline was observed in the study group. When analyzing the level of protein fractions in children undergoing major surgery on abdominal organs, it was found that the albumin fraction was within normal limits. These data may indicate that the correction of protein levels with albumin solutions in this group of children is not appropriate. As for other indicators of the proteogram, the phenomenon of dysproteinemia was observed in all examined children.
Role of parenteral nutrition in the complex of perioperative intensive therapy in children
Keywords: парентеральне харчування; діти; оперативні втручання; parenteral nutrition; child; general surgery